Synthesis and structures of ruthenium di‐ and tricarbonyl complexes derived from 4, 5‐diazafluoren‐9‐one. Issue 11 (13th October 2015) - Jimenez, Jorge; Chakraborty, Indranil; Mascharak, Pradip
Abstract : Carbon monoxide (CO) has recently been shown to impart beneficial effects in mammalian physiology and considerable research attention is now being directed toward metal–carbonyl complexes as a means of delivering CO to biological targets. Two ruthenium carbonyl complexes, namely trans ‐dicarbonyldichlorido(4, 5‐diazafluoren‐9‐one‐κ 2 N, N ′)ruthenium(II), [RuCl2 (C11 H6 N2 O)(CO)2 ], (1), and fac ‐tricarbonyldichlorido(4, 5‐diazafluoren‐9‐one‐κ N )ruthenium(II), [RuCl2 (C11 H6 N2 O)(CO)3 ], (2), have been isolated and structurally characterized. In the case of complex (1), the trans ‐directing effect of the CO ligands allows bidentate coordination of the 4, 5‐diazafluoren‐9‐one (dafo) ligand despite a larger bite distance between the N‐donor atoms. In complex (2), the cis disposition of two chloride ligands restricts the ability of the dafo molecule to bind ruthenium in a bidentate fashion. Both complexes exhibit well defined 1 H NMR spectra confirming the diamagnetic ground state of Ru II and display a strong absorption band around 300 nm in the UV.